Bellis perennis extract mitigates UVA-induced keratinocyte damage: Photoprotective and immunomodulatory effects - Souza de Carvalho, Vivian Maria; Covre, Joyce L.; Correia-Silva, Rebeca D.; Lice, Izabella; Corrêa, Mab P. [UNESP]; Leopoldino, Andréia M.; Gil, Cristiane D. [UNESP] (Elsevier, 2021)
A need exists for further research elucidating the benefits of environmentally safe photoprotective agents against ultraviolet (UV) exposure, and plant extracts represent a human-friendly alternative formulation. This study was designed to evaluate the potential use of Bellis perennis extract (BPE), from the Asteraceae family, known as the common daisy or the English daisy, in cosmeceuticals as a photoprotective factor, using an in vitro model of UVA-induced keratinocyte damage. Human skin keratinocytes (HaCaT cell line) were incubated with BPE at 0.01, 0.1, or 1% in Dulbecco's Modified Eagle Medium (DMEM), and after 15 min they were submitted to UVA radiation at 5, 10, and 15 J/cm2 doses, respectively. For comparative purposes, Polypodium leucotomos extract (PLE), known as the fern, was used as a positive control in assessing the photoprotective effect. After 24 h of UVA exposure, cell viability (MTT and LDH assays), levels of cleaved caspase-3, cyclooxygenase-2, IL-6, reactive oxygen species (ROS) and antioxidant enzyme (catalase, SOD, and glutathione peroxidase) activity were determined. UVA radiation at 5, 10, and 15 J/cm2 doses reduced cell viability to 63%, 43%, and 23%, respectively; we selected 10 J/cm2 for our purposes. After 24 h of UVA exposure, treatment with 1% BPE and 1% PLE significantly recovered cell viability (p < 0.05). Furthermore, treatment was associated with lower cleaved caspase-3 and ROS levels, higher catalase activity, and lower IL-6 levels in the treated UVA keratinocytes compared with the untreated UVA group (p < 0.01). Our results demonstrate photoprotective and immunomodulatory effects of BPE in skin keratinocytes and support its use as a bioactive agent in cosmetic formulations to prevent skin damage caused by exposure to the UV light.
Keywords: Antioxidant defense; Cleaved caspase-3; HaCaT; IL-6; ROS; UVA